Regional Heads’ Legitimacy in Implementing the Regional Government Based on Democratic Principles - Enggarani, Nuria Siswi; Spaltan, Bita Gadsia; Setiawati, Diana; Zuhdi, Syaifuddin; Farid, Achmad Miftah; Budiono, Arief (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The concept of regional autonomy is explicitly regulated in Article 18 of the 1945 Constitution and several related laws and regulations which essentially provide authority and flexibility for provincial, district and city governments to regulate and manage their own government affairs according to the principles of autonomy and assignment tasks including the implementation of regional head elections carried out democratically. In the implementation of regional government, elected regional heads must also be able to realize the principles of democracy and must be able to run effective and responsive regional government to the needs of the community, must not deviate from moral norms and deviate from democratic principles. The problem in this study is How is the Legitimacy of Regional Heads in the Implementation of Regional Government in Accordance with the Principles of Democracy. This study uses an empirical legal method, namely in addition to reviewing data through literature, it also reviews data on events that actually occur through observation activities and so on. The purpose of this study is to analyze legislation and examine cases that have occurred in Indonesia regarding the legitimacy of regional heads in the implementation of regional government in accordance with democratic principles. The conclusion of this study is that based on the analysis of several laws regarding regional heads in the implementation of regional government and based on the analysis of cases of regional heads in leading regional government, they are not yet legitimate and are not in accordance with the principles of democracy